Reproductive Behavior of Bubalus arnee (Kerr, 1792) (Mammalia: Artiodactyla: Bovidae) in Koshi Tappu Wildlife Reserve and Chitwan National Park, Nepal - Ram Krishna Bhattarai; Rajeev Joshi; Jeetendra Gautam; Birendra Kandel; Bikram Singh (International Journal of Zoology)
The Asiatic wild water buffalo (Bubalus arnee Kerr), an endangered species featured on the IUCN Red List, is distributed across Nepal, India, Sri Lanka, Myanmar, Bhutan, Cambodia, and Thailand. This investigation delves into the reproductive and certain social behaviors exhibited by Bubalus arnee across distinct habitats and herd types within Nepal’s Koshi Tappu Wildlife Reserve (KTWR) and Chitwan National Park (CNP) during the premonsoon and postmonsoon spans of 2018. The data were amassed through direct observations employing focal animal sampling, continuous sampling, and scan sampling methodologies. Eight primary behavioral activities were noted: chasing, courtship, grazing, mating, mowing, sniffing, urination, and wallowing. We carefully structured the gathered data and input it into a Microsoft Excel spreadsheet to facilitate analysis. For a more comprehensive visualization of reproductive behavior, we utilized the ggplot2 package within R-studio, enabling the creation of informative graphical depictions. During the premonsoon phase, Bull A exhibited six reproductive behaviors in KTWR. Notably, sniffing was the most frequently observed behavior, recorded six times (37.5%) daily, succeeded by fighting and urination with four (25%) and three (18.35%) daily observations, respectively. Chasing, mating, and courtship were each observed once (6.25%) daily. In contrast, during both seasons, Bulls B, M, and J were not observed partaking in mating activities. When analyzing the postmonsoon reproductive behavior of the observed B. arnee in KTWR and CNP, a notable distinction emerged. In KTWR, there were four more instances of sniffing behavior compared to CNP. In addition, courtship behavior was slightly more frequent in KTWR, occurring three times, whereas it was observed only twice in CNP. Similarly, urination activity was recorded twice as often in KTWR as compared to CNP. As a suggestion for future research, exploring the specific factors influencing the observed variations in reproductive behaviors and habitat preferences of Bubalus arnee could provide valuable insights into the conservation and management of these endangered species.